Metagenomic next-generation sequencing aids the diagnosis of viral infections in febrile returning travellers. Issue 4 (October 2019) - Jerome, Hanna; Taylor, Callum; Sreenu, Vattipally B.; Klymenko, Tanya; Filipe, Ana Da Silva; Jackson, Celia; Davis, Chris; Ashraf, Shirin; Wilson-Davies, Eleri; Jesudason, Natasha; Devine, Karen; Harder, Lisbeth; et al.
Highlights: Next generation sequencing (NGS) has potential as an all-in-one diagnostic test for infection. Viral, bacterial and parasite genomes can be detected rapidly. NGS is becoming increasingly affordable but requires validation in clinical laboratories. Abstract: Objectives: Travel-associated infections are challenging to diagnose because of the broad spectrum of potential aetiologies. As a proof-of-principle study, we used MNGS to identify viral pathogens in clinical samples from returning travellers in a single center to explore its suitability as a diagnostic tool. Methods: Plasma samples from 40 returning travellers presenting with a fever of ≥38°C were sequenced using MNGS on the Illumina MiSeq platform and compared with standard-of-care diagnostic assays. Results: In total, 11/40 patients were diagnosed with a viral infection. Standard of care diagnostics revealed 5 viral infections using plasma samples; dengue virus 1 ( n  = 2), hepatitis E ( n  = 1), Ebola virus ( n  = 1) and hepatitis A ( n  = 1), all of which were detected by MNGS. Three additional patients with Chikungunya virus ( n  = 2) and mumps virus were diagnosed by MNGS only. Respiratory infections detected by nasal/throat swabs only were not detected by MNGS of plasma. One patient had infection with malaria and mumps virus during the same admission. Conclusions: MNGS analysis of plasma samples improves the sensitivity of diagnosis of viral infections and has potential as an all-in-one diagnostic test. It can be used to identify infections that have not been considered by the treating physician, co-infections and new or emerging pathogens. Summary: Next generation sequencing (NGS) has potential as an all-in-one diagnostic test. In this study we used NGS to diagnose returning travellers with acute febrile illness in the UK, highlighting cases where the diagnosis was missed using standard methods.